Pertumbuhan Ekonomi: Ditinjau Dari Belanja Kesehatan, Belanja Pendidikan, dan Belanja Modal Pada Pemerintah Daerah - Aulia, Widiatul; Rizky, Fitrian; Maulina, Rina (Universitas Teuku Umar, 2024)
This research was conducted with the aim of empirically examining whether healthcare expenditure, education expenditure, and capital expenditure influence economic growth in regencies/cities in Indonesia. Secondary data from Budget Realization Reports and Economic Growth from 2018 to 2022 were utilized for this study. Using a census method for sampling technique, the sample size consisted of 508 regencies/cities in Indonesia with a five-year observation period as the research sample. As this research employed panel data, the data analysis utilized panel data regression with the assistance of Stata Version 17 statistical software. The research findings indicate that capital expenditure significantly influences economic growth, whereas healthcare expenditure and education expenditure were found to have no significant impact on economic growth. The implication of this research is that government spending in the education, health and capital sectors has significant practical and theoretical implications for economic growth in Indonesia. This shows that increasing investment in these sectors can encourage positive economic growth.